Case for diagnosis Caso para diagnóstico - Emanuela Plech Thomé; Raquel Bissacotti Steglich; Carolina Degen Meotti; Joel Schwartz; Ana Letícia Boff (Sociedade Brasileira de Dermatologia, 2012)
Papular elastorrhexis is a rare acquired disease, first described in 1987 by Bordas, which has been very rarely reported in the literature. It is characterized by small asymptomatic non-follicular papules, mainly distributed in the trunk. Histology of the lesions shows homogenization of collagen and fragmentation of elastic fibers in the dermis. The rarity of this disease is probably due to the subtlety and benign nature of clinical and histopathological alterations, which can be easily confused with other pathologies. The authors report the case of a patient with exuberant clinical manifestations typical of elastorrhexis papular. Elastorrexe papulosa é uma doença adquirida rara, descrita em1987 por Bordas e poucas vezes relatada na literatura. Caracteriza-se por pequenas pápulas, não foliculares, assintomáticas, distribuídas essencialmente no tronco. A histologia das lesões demonstra homogeneização do colágeno e fragmentação de fibras elásticas dérmicas. A raridade dessa entidade provavelmente se deve à sutileza e benignidade das alterações clínicas e histopatológicas, que podem facilmente ser confundidas com inúmeras outras afecções. Os autores relatam o caso de uma paciente com quadro clínico exuberante e característico de elastorrexe papulosa.